Year in Review 2018 by the Brazilian Gastrointestinal Tumors Group: Neuroendocrine Tumors - Rocha, Duilio R., Filho; Rego, Juliana F.; Riechelmann, Rachel P. (Brazilian Journal of Oncology, 2018)
Neuroendocrine tumors (NET) constitute a heterogeneous group of neoplasms with variable prognoses and clinical presentations. Therefore their therapeutic management is challenging, involving a real multidisciplinary approach composed of medical oncologists, surgeons, endocrinologists, nuclear medicine physicians and interventionist radiologists. Here in this article, we have summarized the studies that have changed (or are likely to influence) the clinical management of patients with NET in 2018: the new WHO pathology classification for pancreatic NET, the use of peptide receptor radionuclide therapy (PRRT) in G3 NET, re-treatment with PRRT, randomized data on the CapTem regimen and new data on carcinoid heart disease.
Keywords: Neuroendocrine Tumors; Malignant Carcinoid Syndrome; Antineoplastic Agents